2017
DOI: 10.3352/jeehp.2017.14.29
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an asynchronous electronic curriculum in emergency medicine education in the United States

Abstract: PurposeThe aim of this study was to measure the effect of an iPad-based asynchronous curriculum on emergency medicine resident performance on the in-training exam (ITE). We hypothesized that the implementation of an asynchronous curriculum (replacing 1 hour of weekly didactic time) would result in non-inferior ITE scores compared to the historical scores of residents who had participated in the traditional 5-hour weekly didactic curriculum.MethodsThe study was a retrospective, non-inferiority study. conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…Although we have no reason to suspect differences in resident roles or workload between the sites, we did not directly assess this either. Curricular length has also been described as a barrier to curriculum completion ( 19 , 20 ); however, we observed higher completion rates by residents at the site with the longer curriculum.…”
Section: Discussioncontrasting
confidence: 49%
“…Although we have no reason to suspect differences in resident roles or workload between the sites, we did not directly assess this either. Curricular length has also been described as a barrier to curriculum completion ( 19 , 20 ); however, we observed higher completion rates by residents at the site with the longer curriculum.…”
Section: Discussioncontrasting
confidence: 49%
“…Residents were required to complete these modules, and their progress was monitored in addition to ITE scores. The group found that despite the decrease in traditional conference hours, time now allotted to III, there was no negative impact on resident ITE scores 28…”
Section: Current Uses Of III In Emergency Medicinementioning
confidence: 99%
“…Much of the success of asynchronous learning comes from an individual’s ability to work at their own pace and in accordance with their own schedule [ 21 , 22 ]. Synchronous didactics are often face-to-face meetings that require interactions, cooperation among groups, and responses to social cues that can present unique challenges during remote meetings.…”
Section: Update the Curriculummentioning
confidence: 99%